PENGARUH DUKUNGAN MANAJEMEN PUNCAK, KEMAMPUAN TEKNIK PERSONAL SERTA PROGRAM PELATIHAN DAN PENDIDIKAN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Vegathree, Chandrika Raveena; Sari, Rafika; Ratu, Mutiara Kemala (LPPM Universitas Bina Bangsa, 2025)
The performance of an accounting information system can be evaluated through two aspects, namely system user satisfaction and the level of system utilization. Satisfaction assessment is related to the extent to which users feel that this system meets all their needs in supporting the completion of their work. On the other hand, evaluation of system utilization is related to the behavior of individuals who use accounting information systems because they see benefits that can help them in completing their work tasks. This research aims to examine the influence of top management support, personal technical abilities and training and education programs as independent variables on the performance of accounting information systems as the dependent variable. This research is quantitative in nature with data sources coming from questionnaires and interviews. Data sources were collected directly through questionnaires or questionnaires from Hotel Hayo employees. The results of the analysis show that partially the sig value of top management support indicates that the independent variable has a positive and significant influence on the dependent variable of accounting information system performance. Personal technical ability variables and training and education programs have a positive and significant influence on accounting information system performance variables. Simultaneously, the independent variables together have a positive effect on improving the performance of the accounting information system